The legacy of Covid-19 in education - Katharina Werner; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
If school closures and social-distancing experiences during the Covid-19 pandemic impeded children's skill development, they may leave a lasting legacy in human capital. To understand the pandemic's effects on school children, this paper combines a review of the emerging international literature with new evidence from German longitudinal time-use surveys. Based on the conceptual framework of an education production function, we cover evidence on child, parent, and school inputs and students' cognitive and socio-emotional development. The German panel evidence shows that children's learning time decreased severely during the first school closures, particularly for low-achieving students, and increased only slightly one year later. In a value-added model, learning time increases with daily online class instruction, but not with other school activities. The review shows substantial losses in cognitive skills on achievement tests, particularly for students from disadvantaged backgrounds. Socio-emotional wellbeing also declined in the short run. Structural models and reduced-form projections suggest that unless remediated, the school closures will persistently reduce skill development, lifetime income, and economic growth and increase inequality.
Keywords: I20; H52; J24; 330; Covid-19; school closures; education; schools; students; educational inequality